Co-operative inquiry: A research policy method for secondary education in Nigeria - Olayiwola, Shina (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2022)
This article examines the level of research involvement among educational stakeholders in the process of educational policy-making and implementation in Nigeria. It attributes the transformational challenges confronting the secondary school system in Nigeria to the epistemological question: “What is the relationship between the knower or would-be knower and what can be known?” This is premised on the idea that the research process that led to the 6-3-3-4, or the “new” 9-3-4 system of education from the 6-5-2-3 system of education, did not involve the participants as co-researchers and co-subjects in their relationship. This article argues for co-operative inquiry as an alternative participatory, action research method for ameliorating these transformational challenges in the Nigerian secondary school system.